Emerging role of N-myc downstream-regulated gene 2 (NDRG2) in cancer - Hu, Wei (Oncotarget, 2015)
N-myc downstream-regulated gene 2 (NDRG2) is a tumor suppressor and cell stress-related gene. NDRG2 is associated with tumor incidence, progression, and metastasis. NDRG2 regulates tumor-associated genes and is regulated by multiple conditions, treatments, and protein/RNA entities, including hyperthermia, trichostatin A and 5-aza-2′-deoxycytidine, which are promising potential cancer therapeutics. In this review, we discuss the expression as well as the clinical and pathological significance of NDRG2 in cancer. The pathological processes and molecular pathways regulated by NDRG2 are also summarized. Moreover, mechanisms for increasing NDRG2 expression in tumors and the potential directions of future NDRG2 research are discussed. The information reviewed here should assist in experimental design and increase the potential of NDRG2 as a therapeutic target for cancer.